Mediastinoscopy. Issue 3 (May 1970) - Ross, J. Keith; Mikhail, John R.; Drury, R. A. B.; Levis, R. D.; Mitchell, D. N.
Abstract : The surgical and anaesthetic technique used in mediastinoscopy during the investigation of 124 patients is described. A histological diagnosis was made in 109 cases (88%). Of the 22 cases other than sarcoidosis a positive diagnosis was obtained in all. In 102 cases with suspected sarcoidosis, the histological appearances of the nodes were compatible with sarcoid in 86 (84%). No serious complications were encountered. It is concluded that this procedure should be carried out by an experienced thoracic surgeon and will yield better diagnostic tissue than other comparable procedures.